Portable Device for Measuring Heart Rate of Pregnant Women Based on Ip Address With BPM Graph Display - Wahyuni, Yuli (Indonesian Journal of Artificial Intelligence and Data Mining, 2024)
Checking the pregnant woman's womb during pregnancy is very important and should be done regularly. In the examination, the calculation of the number of heartbeats in a certain time interval is called beats per minute. The matrix of a person's heart condition is BPM (beats per Minute). This research is related to making a prototype of a pregnant woman's heart rate device using a fingerprint sensor. The tool can be used for health experts, namely midwives. The test results of abnormal heart rate of pregnant women are 1 person. This tool is very easy to use because it is portable (easy to carry everywhere) and its use by attaching the fingerprints of pregnant women to the max30100 sensor for 10-15 seconds using the index finger, the sensor will process the data read by the NodeMCU receiving data and the data transmission process is displayed on the IP Addres in the form of BPM. NodeMCU must be connected via wifi / hotspot with one Ip address and must have an account to be able to access on the internet platform, namely google chrome or mozila firefox so that it can be accessed via smartphone or personal computer.